2018
DOI: 10.1159/000490028
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of NF-κB/P65 and LncRNA HOTAIR-Mediated Repression of MUC1 Expression Contribute to Synergistic Inhibition of Castration-Resistant Prostate Cancer by Polyphyllin 1–Enzalutamide Combination Treatment

Abstract: Background/Aims: Polyphyllin I (PPI), one of the steroidal saponins in Paris polyphylla, reportedly exhibits antitumor effects. However, the detailed mechanism underlying PPI, particularly in enhancing the effect of the androgen receptor inhibitor enzalutamide in controlling castration-resistant prostate cancer (CRPC) has not been explored. Methods: Cell viability and cell cycle distribution were measured using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and flow cytometry assays, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…In considering how high glucose may upregulate HOTAIR, we were cognisant of work reporting a role for the p65 subunit of NF-κB in regulating the expression of human HOTAIR [33,34]. We performed in silico analysis of the mouse Hotair promoter and identified three potential binding sites for NF-κB (ESM Fig.…”
Section: Exposure To High Glucose Increases Hotair Expression By Mousmentioning
confidence: 99%
“…In considering how high glucose may upregulate HOTAIR, we were cognisant of work reporting a role for the p65 subunit of NF-κB in regulating the expression of human HOTAIR [33,34]. We performed in silico analysis of the mouse Hotair promoter and identified three potential binding sites for NF-κB (ESM Fig.…”
Section: Exposure To High Glucose Increases Hotair Expression By Mousmentioning
confidence: 99%
“…HULC silencing suppressed angiogenesis by regulating ESM-1 via the PI3K/Akt/mTOR signaling pathway in human gliomas [34]. Recently, a growing number of novel treatment strategies, such as compounds derived from natural products, have been developed for cancer therapy by targeting lncRNAs [35][36][37]. Previous study reported that β-elemene inhibited the growth of esophageal cancer by modulating lncRNA-mediated inhibition of hTERT [38].…”
Section: Discussionmentioning
confidence: 99%
“…The 5TR1 aptamer binds to the aberrantly hypoglycosilated MUC1 located on the breast cancer-cell surface. The second lock corresponds to the hMUC1 promoter, which ensures expression of the cytotoxic ricin with the preprotrypsin leader only in MUC1 overexpressing cells [53,54].…”
Section: Discussionmentioning
confidence: 99%